Soil management in organic carbon conservation - Zamora-Morales, Bertha P.; Mendoza-Cariño, Mayra; Sangerman-Jarquín, Dora Ma.; Quevedo Nolasco, Abel; Navarro Bravo, Agustín (Revista Mexicana de Ciencias Agrícolas, 2018)
The anthropogenic emissions of carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O), distinguish these greenhouse gases (GEI) as the main causes of global warming. Which come from the energy (25.9%), industrial (19.4%), forestry (17.4%) and agricultural (13.5%) sectors worldwide. Of the total GEI flows, the agricultural sector contributes 25% of CO2, 55-60% of CH4 and 65-80% of N2O. The CO2 is generated mainly by deforestation in tropical regions, CH4, by livestock and rice crops, N2O by the use of fertilizers. Mexico is located within the 15 countries with the highest GEI production. Approximately 30% of its total emissions correspond to the agricultural, livestock and forestry sectors: two thirds are produced by land use activities (including change in use) and forestry the rest, by agriculture and livestock conventional. Due to the fact that soil organic carbon is related to the sustainability of agricultural systems, and in its content, affects soil management, various practices have been developed to favor their storage in the country's agricultural and forestry sectors. However, it is necessary to implement public policies that benefit the adoption and promotion of these practices and, at the same time, facilitate the fulfillment of the commitments that Mexico has acquired nationally and internationally, to minimize its GEI emissions.
Keywords: organic soil carbon; greenhouse gases; conservation tillage; carbon sequestration; land use